Cadaveric bone marrow as potential source of hematopoietic stem cells for transplantation - Michalova, Jana; Savvulidi, Filipp; Sefc, Ludek; Forgacova, Katarina; Necas, Emanuel (Chimerism, 2011)
Every year, bone marrow transplantation saves many lives worldwide. Unfortunately, a suitable donor is not always available. Since organs are routinely harvested from cadaveric organ donors, we decided to assess such a possibility for bone marrow. We analyzed the functional properties and phenotypic markers of murine hematopoietic stem and progenitor cells (HSPC) from cadaveric bone marrow and during storage in vitro in a suspension. It was demonstrated that HSPC exposed to a warm or cold ischemia in intact femur did not lose their phenotype and maintained their repopulating ability for two to twelve hours depending on the temperature. Additionally, fresh bone marrow remained fully viable in cell suspension for two days or four days at 37°C or 4°C, respectively. Based on these findings, cadaveric bone marrow could be considered as an alternative source of hematopoietic stem cells for transplantation.